Dampak Financial Technology (Fintech) terhadap Pengangguran di Beberapa Negara Berkembang - Putri, Prince Amalia; Santi, Fitri (Jurnal Maksipreneur, 2025)
This study aims to analyze the effect of financial technology (fintech) adoption on unemployment rates in 77 developing countries with observation periods in 2014, 2017, and 2021. Fintech is represented by four main indicators, namely bank account ownership (BA), internet use for payments (IU), digital transactions (DP), and mobile money account ownership (MMA). The research data were sourced from the Global Findex Database and the World Bank, analyzed using panel data regression with a Random Effect Model (REM) approach through the Generalized Least Squares (GLS) method. The results of the study show that economic growth (GDP growth) has a significant negative effect on unemployment rates, in accordance with Okun's law. In terms of fintech, bank account ownership (BA) has a significant negative effect on unemployment, confirming the role of formal financial access in increasing employment opportunities. Conversely, internet use for payments (IU) has a significant positive effect on unemployment, indicating that passive utilization has not been able to encourage the creation of new jobs. Meanwhile, the variables of digital transactions (DP) and mobile money account ownership (MMA) did not show a significant effect on unemployment. Overall, the results of the study confirm that fintech has the potential to reduce unemployment rates in developing countries, but its impact is highly dependent on the form of adoption and the level of active use. The results have significant implications for financial inclusion policies and the role of financial technology in creating job opportunities.